THE EFFECT OF STORYTELLING METHOD ASSISTED WITH PICTURE MEDIA TOWARDS SPEAKING SKILL OF 4TH GRADE STUDENTS - Maulida Rizka Mardiyanti; Ida Ermiana; Heri Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2021)
This study aims to determine the effect of the pictorial media-assisted storytelling method on the speaking skills of fourth-grade students of SDN 2 Bagik Payung Timur. The results of this study are expected to be useful theoretically and practically. This type of research was an experimental study with repeated treatment research design. The subjects in this study were fourth-grade students of SDN 2 Bagik Payung Timur. The data collection methods were observation and speaking skills tests. The speaking skill test was used to obtain data related to students' speaking skills, while observation was used to obtain data on the feasibility of learning carried out by the teacher. The data obtained were analyzed using ANOVA repeated measure formula to determine whether there was an effect of the pictorial media-assisted storytelling method on students' speaking skills. Based on the results of the ANOVA repeated measure test, a significance value of 0.000 was obtained, which is smaller than 0.05. This shows that Ho is declared rejected Ha declared accepted. So it can be concluded that the image media-assisted storytelling method affects the speaking skills of fourth-grade students of Bagik Payung Timur for the academic year 2020/2021.